2014
DOI: 10.3390/ijerph110706757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Residential Greenness on Preschool Children’s Emotional and Behavioral Problems

Abstract: This study investigated the effects of the proximity to city parks and the influence of residential greenness on children’s emotional and behavioral problems. This cross-sectional study included 1,468 mothers of children (ages 4 to 6) who were residents of the city of Kaunas, Lithuania. The mothers and their children were enrolled in the FP7 PHENOTYPE project study. The mothers reported on their parenting stress and their children’s mental health. Residential greenness was characterized as an average of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(161 citation statements)
references
References 36 publications
6
142
5
1
Order By: Relevance
“…For example, in Germany, Markevych and colleagues found poorer access to urban green spaces was associated with more behavioural problems—and hyperactivity/inattention problems in particular—among 10-year-old children whose parents had filled in the SDQ [11]. Balseviciene and colleagues’ study in Lithuania required mothers to fill in the SDQ on behalf of their four- to seven-year-old children, finding poorer mental wellbeing associated with lower residential greenness among those whose mothers had low levels of education [12]. Amoly and colleagues’ study of children aged seven to 10 years in Barcelona found fewer parent-reported SDQ-derived total difficulties, emotional symptoms and peer relationship problems among those spending more playing time within green spaces [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Germany, Markevych and colleagues found poorer access to urban green spaces was associated with more behavioural problems—and hyperactivity/inattention problems in particular—among 10-year-old children whose parents had filled in the SDQ [11]. Balseviciene and colleagues’ study in Lithuania required mothers to fill in the SDQ on behalf of their four- to seven-year-old children, finding poorer mental wellbeing associated with lower residential greenness among those whose mothers had low levels of education [12]. Amoly and colleagues’ study of children aged seven to 10 years in Barcelona found fewer parent-reported SDQ-derived total difficulties, emotional symptoms and peer relationship problems among those spending more playing time within green spaces [13].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Goodman’s 25-item Strengths and Difficulties Questionnaire (SDQ) is an internationally recognised behavioural screening tool of child wellbeing [10]. A cursory review of the literature shows the parent-reported version of the SDQ has been used to examine associations between mental wellbeing and neighbourhood green space among children in Germany [11], Lithuania [12], Spain [13] and England [14]. All have reported protective associations.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, three indicators of exposure were developed including surrounding greenness, access to green spaces, and access to blue spaces. We characterized these indicators in a circular buffer of 300 m around geocoded address of residence of each participant, following previous studies for surrounding greenness (Balseviciene et al, 2014) and European Commission recommendations for access to green spaces (European Commission, 2001), and taking into account that it has been suggested that after 300-400 m of distance the use of natural outdoor environments decline (Annerstedt et al, 2012).…”
Section: Natural Outdoor Environment Indicatorsmentioning
confidence: 99%
“…In fact, the few studies exploring associations between preschoolers’ well‐being and nature exposure were cross‐sectional and yielded mixed results. Among investigations outside the school setting, one study examined associations between Lithuanian children's mental health and home nature and found that proximity to parks was related to better child mental health among 4‐ to 6‐year‐old children from families of low‐socioeconomic status (SES); however, children from high‐SES backgrounds living in homes near more green space had worse mental health (Balseviciene et al., ). Another study found that young children (ages 4.5–6.5 years) with greener schoolyards exhibited fewer behaviors marked by inattention, impulsivity, and hyperactivity (Mårtensson et al., ).…”
Section: Introductionmentioning
confidence: 99%